Why the EU’s international legitimacy matters: the case of crisis management - Ribeiro, Inês Marques (2018)
In many externally oriented policies, the European Union puts itself at the centre, branding as an ideal that it tries to reproduce in its relationship with third countries. The EU’s crisis management policy – the Common Security and Defence Policy (CSDP) – is no different: it is amplybased on the premise that crises can only be solved in a stable and long-lasting manner if countries develop liberal democratic institutions based on European standards and models.